Three-dimensional fractal model of contact stress of cylinder joint - WANG Xue; LI XiaoPeng; XU JinChi (Jixie qiangdu)
In order to study the carrying capacity of the cylinder joint in the mechanical structure, based on Hertz contact theory and combined with the modified three-dimensional fractal theory, the three-dimensional fractal theory was applied to simulate the actual engineering joint surface, and a three-dimensional fractal model of the contact stress of the cylinder joint was established under the comprehensive consideration of the macroscopic characteristics and the microscopic morphology factors. And a comparative analysis was conducted with the Hertz contact model, proving the rationality of the established model. Through Matlab simulation analysis, from the macro characteristics, the contact stress can be reduced and the carrying capacity can be improved by using the form of internal contact cylinder joint or by increasing the radius of the cylinder. From the aspect of microscopic morphology, the contact stress can be reduced by reducing the fractal dimension parameter and the material characteristic parameter. The influence of the fractal dimension of the micro-topography parameter on the contact stress is complex. When 2. 1 ≤ D ≤2.5, increasing the fractal dimension can reduce the contact stress. When 2.5 ≤ D ≤ 2. 9, reducing the fractal dimension can reduce the contact stress.